THE ROLE OF VITAMIN E (α-TOCOPHEROL) ON TESTOSTERONE LEVEL IN SPRAGUE DAWLEY RATS FOLLOWING CISPLATIN TREATMENT - Rezia, Dian Kartika; Hakim, Lukman; Djatisoesanto, Wahjoe (Indonesian Urological Association, 2019)
Objective: To observe the difference of testosterone levels in adult male Sprague Dawley rats treated with combination of cisplatin and vitamin E compared to those treated with cisplatin only. Material & Methods: We used 24 adult male Sprague Dawley rats weight 200–300 grams and randomly assigned into 4 groups (n=6). Rats in negative control group (NC) were given intraperitoneal normal saline injection, while the positive control (PC) group were injected with cisplatin 5 mg/kgBW at the end of the 3rd week. Two other groups, P1 and P2, were injected with cisplatin 5 mg/kgBW and given vitamin E orally 50 mg/kgBW and 200 mg/kgBW, respectively. Cardiac blood was aspirated at the end of the 7th week and processed for analysis of testosterone levels. Results: We recorded a significantly lower testosterone levels in rats treated only with cisplatin 5 mg/kgBW (CP) compared to those in CN group (p=0.006), and those receiving combination of cisplatin and vitamin E 50 mg/kgBW (p=0.003) and 200 mg/kgBW (p=0.001). Though not significant, testosterone levels were higher in P2 group than in P1 group (p=0.702). Conclusion: Exposure to cisplatin can lower testosterone levels in white rats, and the administration of vitamin E gives protection against such effect.